The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-2168.1999.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Day-case haemorrhoidectomy

Abstract: Ligation excision haemorrhoidectomy can be performed successfully as a day-case procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 21 publications
3
44
0
3
Order By: Relevance
“…6 Investigators have demonstrated reduced postoperative pain in randomized trials as a result of local anesthetic infiltration, 7,8 local anesthetic regional blockage, 9 transdermal fentanyl, 10 and diathermy excision, 11,12 which has facilitated the performance of day-case hemorrhoidectomy. 13 Closed hemorrhoidectomy has theoretical advantages over the MilliganMorgan technique by reducing the areas of denuded anal wall, which may reduce spasm and fissuring. 14 A review of the randomized, controlled trials addressing this issue, however, showed no differences in pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…6 Investigators have demonstrated reduced postoperative pain in randomized trials as a result of local anesthetic infiltration, 7,8 local anesthetic regional blockage, 9 transdermal fentanyl, 10 and diathermy excision, 11,12 which has facilitated the performance of day-case hemorrhoidectomy. 13 Closed hemorrhoidectomy has theoretical advantages over the MilliganMorgan technique by reducing the areas of denuded anal wall, which may reduce spasm and fissuring. 14 A review of the randomized, controlled trials addressing this issue, however, showed no differences in pain scores.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a postoperative program that may still be troubled by varying degrees of pain, time off work, and a low incidence of urinary retention, modification of technique and modern analgesia have allowed an approach using day surgery for most, 19 greatly reducing the costs. However, the costs of banding equipment are negligible if nondisposable instruments are used that only necessitate a simple sterilizer on site.…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al, 1997;Hicklin et al, 1999;Hunt et al, 1999;Lau et al, 2000). Patients´ satisfaction is affected by the following aspects: continuous postoperative pain control (McHugh & Thoms, 2002), a short waiting period before surgery, the friendly behavior of the staff, phone check of the health status following after surgery.…”
Section: Social Resultsmentioning
confidence: 99%